PENGARUH KEPERCAYAAN, KUALITAS PRODUK, KUALITAS INFORMASI, DAN KEMUDAHAN TRANSAKSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHIONONLINE DI MEDAN MELALUI APLIKASI SHOPEE: (Studi Kasus : Mahasiswa Fakultas Ekonomi dan Bisnis Prodi Manajemen Unika Santo Thomas ) - Sinaga, Risna Tarida; Simanihuruk, Peran; Tamba, Darwis (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2023)
This research aims to determine the influence of trust, service quality, information quality and ease of transactions on online fashion product purchasing decisions in Medan via the Shopee application. The population is all students at the Faculty of Economics, Management Study Program, Unika Santo Thomas and the maximum desired sample size is 96 people. Analysis techniques using descriptive analysis and multiple linear regression. The research results show that the variables of trust, service quality, information quality and ease of transactions have a positive influence on purchasing decisions for online fashion products in Medan via the Shopee application. Based on the value = 56.982 > = 2.74, Ho is rejected and H1 is accepted, meaning that trust, product quality, information quality and ease of transactions simultaneously have a positive and significant effect on purchasing decisions. Based on the trust value (5.771 > l (2.060), H0 is rejected and H1 is accepted. This means that trust has a positive and significant effect on purchasing decisions. The value (3.338) of product quality > (2.060) means that H0 is rejected and H1 is accepted. This means that product quality has a positive and significant effect on purchasing decisions. The value of information quality is (4.768) > (2.060), so H0 is rejected and H1 is accepted. This means that the quality of information has a positive and significant effect on product purchasing decisions. The value of ease of transaction is (2.812) > (2.060) then H0 is rejected and H1 is accepted. This means that ease of transaction has a positive and significant effect on purchasing decisions. The coefficient of determination (R Square) = 0.901 means that 90.1% of purchasing decisions can be explained by the variables trust, service quality, information quality and ease of transaction and the rest Another 9.9% can be explained by other factors such as price and promotions, which were not included in the study.